Mondains and oblates. Body trajectories in high-level sport - Longchamp, P.; Braizaz, M.; Tawfik, A.; Toffel, K. (International Review for the Sociology of Sport, 2023)
Most of the scientific literature concerning former high-level athletes is devoted to their professional retraining. There are comparatively few empirical studies dealing with their body representations and practices. Based on Pierre Bourdieu`s theoretical framework, this article presents the results of an interview survey with 30 former high-level athletes. It shows that their relationships with their bodies result from their specific body trajectories, marked by family socialization and social background, sports socialization, injuries, and the possession of different forms of capital. In contrast to mondains, who have relatively stable body trajectories, oblates are marked by less homogeneous socialization and see their body trajectories divided between a form of personal dissatisfaction on the one hand and a feeling of saturation with their sport on the other.